Beliefs and Attitudes of Graduate Gerontology Students about Medical Marijuana Use for Alzheimer's and Parkinson's Disease. (August 2020) - Edelstein, Offer E.; Wacht, Oren; Isralowitz, Richard; Reznik, Alexander; Bachner, Yaacov G.
Highlights: Most of the participants had no formal education about medical marijuana (MMJ) Most of the participants believed that MMJ is effective for AD and PD Prior marijuana use was found associated with beliefs about MMJ benefits and risks Efforts to develop curricula and training programs should be promoted Abstract: Aims: The aims of the current study were as follows: 1) to assess gerontology graduate students' beliefs about medical marijuana's (MMJ) effectiveness for two common age-related conditions - Alzheimer's (AD) and Parkinson's disease (PD); 2) to assess students' beliefs and attitudes toward MMJ; 3) to explore associations linking background characteristics, MMJ-related attitudes and beliefs, and beliefs about the MMJ effectiveness for AD and PD. Method: A sample of 104 (84 women and 20 men) gerontology graduate students voluntarily participated in the anonymous online survey. Results: The vast majority (95%) of the participants indicated they had no formal education about MMJ and reported being unprepared to answer clients' MMJ-related questions (84.6%). Most of the participants believed that MMJ is effective for use with AD (70.2%) and PD (80.8%) patients. Participants reported favorable beliefs about MMJ benefits, concerns about risks, the need for training, and positive attitudes toward recreational marijuana use legalization. Prior marijuana use (e.g., self-use, friends or family) was found to be associated with more positive beliefs about MMJ benefits, risks, and its legalization for recreational purposes. Prior marijuana use was the only factor associated with the belief that MMJ is an effective therapy for use with AD or PD patients. Conclusions: The study findings show the need for students' MMJ education in order to provide future gerontology service providers with the necessary knowledge and ability to address clients' questions about MMJ use. Efforts to develop curricula and training programs need to be promoted.